2021
DOI: 10.1002/adom.202100870
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Induced Self‐Reduction and Anti‐Thermal Quenching in NaZn(PO3)3:Mn2+ Red Phosphor

Abstract: Self‐reduction behavior of doped activators and zero‐thermal‐quenching luminescence have received much more attention in the exploration of luminescent materials for phosphor‐converted white light‐emitting diodes. Here, a combination of the two properties is demonstrated in a Mn2+ activated red phosphor, NaZn(PO3)3:Mn2+, synthesized by a high temperature solid state reaction in ambient atmosphere, which is free from thermal quenching until 250 °C. By combined first‐principles calculation and experimental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 46 publications
2
41
0
1
Order By: Relevance
“…However, it was not fully complete, regardless of the Mn-sources. This self-reduction process has also been found in other Mn 2+ -phosphors such as NaZn(PO 3 ) 3 :Mn 2+ , 22 KZn(PO 3 ) 3 :Mn 2+ (ref. 39) and Zn 4 B 6 O 13 :Mn 2+ .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, it was not fully complete, regardless of the Mn-sources. This self-reduction process has also been found in other Mn 2+ -phosphors such as NaZn(PO 3 ) 3 :Mn 2+ , 22 KZn(PO 3 ) 3 :Mn 2+ (ref. 39) and Zn 4 B 6 O 13 :Mn 2+ .…”
Section: Resultssupporting
confidence: 71%
“…As a case series, polyphosphates AB(PO 3 ) 3 (A = alkali metals, B = alkali-earth metals and Zn), with several different structure types, tend to form a single-Mn 2+ -doped phosphor even under high temperature calcination in the open air, including NaZn(PO 3 ) 3 :Mn 2+ (ref. 22) and KCa(PO 3 ) 3 :Mn 2+ . 23 Wu et al studied the reason of the self-reduction mechanism for NaZn(PO 3 ) 3 :Mn 2+ by the combination of theoretical calculations, and found that the Zn 2+ vacancy defects and energy transfer from the defect to Mn 2+ responded to this process.…”
Section: Introductionmentioning
confidence: 98%
“…And then the two negative charges will transfer to the Mn 4+ position to reduce it to Mn 2+ . 27 As for the KMnO 4 doped phosphor, KMnO 4 would decompose into MnO 2 first and then go through the above means to achieve self-reduction to Mn 2+ . The PL decay curves of the RZPO:MnCO 3 (air, Ar/H 2 ), RZPO:MnO 2 (air, Ar/H 2 ), and RZPO:KMnO 4 (air, Ar/H 2 ) samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to rare earth ions, Mn 4+ , a commonly used red phosphor activator with excellent optical properties and low cost, can be self-reduced in some unique crystal structures in an air environment (Mn 4+ → Mn 2+ ), e.g. , NaMg(PO 3 ) 3 :Mn 2+ , 14 Ba 3 BP 3 O 12 :Mn 2+ , 15 β-KMg(PO 3 ) 3 :Mn 2+ , 16 BaXP 2 O 7 :Mn 2+ (X = Mg/Zn), 17 NaZn(PO 3 ) 3 :Mn 2+ , 18 etc. , exhibiting high thermal stability and anti-quenching phenomena.…”
Section: Introductionmentioning
confidence: 99%